Ruthenium-based bifunctional fuel cell catalyst as well as preparation method and application thereof
By wrapping glucose hydrate with nano MgO in fuel cells, preparing a porous nanocarbon material with nitrogen-containing spherical shell and attaching ruthenium to form a ruthenium-based bifunctional catalyst, solving the difference in cathode and anode catalysts and the scarcity of bifunctional catalysts in fuel cells. Problem, cost-effective electrocatalytic activity and stability are achieved, 70% of the performance of platinum-based catalysts, and cost reduction.
Patent Information
- Application Number
- CN202411773875.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-05
AI Technical Summary
In existing fuel cells, cathode and anode catalysts are different, and dual-function catalysts are scarce, making it difficult to achieve cost-effective replacement or reduce the amount of platinum-based catalysts.
A nitrogen-containing spherical shell-like porous nanocarbon material is prepared by wrapping glucose hydrate with nano MgO, and ruthenium is attached to it by hydrothermal reaction to form a ruthenium-based bifunctional fuel cell catalyst, used as cathode and anode catalysts for fuel cells.
The high electrocatalytic activity and stability of the ruthenium-based catalyst in acidic medium is achieved, the actual discharge performance reaches 70% of the platinum-based catalyst, and the cost of fuel cells is reduced. It has the dual characteristics of oxygen reduction and hydroxide, which is suitable for fuel cells. Industrialized production.
Smart Images

Figure CN119252953A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and in particular relates to a ruthenium-based bifunctional fuel cell catalyst and a preparation method and application thereof. Background Art
[0002] Fuel cells are important electrochemical devices that convert the chemical energy of fuel into electrical energy through electrochemical reactions. They are one of the key technologies to promote sustainable economic development. Unlike traditional thermal cycle systems, fuel cells are not limited by the Carnot cycle and have high energy conversion efficiency. In the prior art, fuel cell catalysts are usually platinum-based catalysts, but to achieve mass production and commercialization of fuel cells, the high price of platinum must be taken into account. In recent decades, people have been committed to developing high-performance and stable electrocatalysts to replace or reduce the amount of platinum-based catalysts for oxygen reduction and hydrogen oxidation in proton exchange membrane fuel cells. Ruthenium, as a precious metal with similar properties to platinum, is much cheaper than platinum, with a price of only about 10% of platinum. Multifunctional catalysts are substances that have the function of catalyzing multiple reactions at the same time. Such substances generally have multiple catalytic active centers, under whose action, multiple steps of different types of catalytic reactions can be completed in one reaction process. Compared with the bifunctional catalytic research on hydrogen evolution and oxygen evolution, the bifunctional catalysis of ruthenium for hydrogen oxidation and oxygen reduction is rarely reported. Therefore, the development of cost-effective ruthenium-based bifunctional fuel cell catalysts is of great significance for the practical application of fuel cells. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of different cathode and anode catalysts and scarcity of bifunctional catalysts in the prior art fuel cells. The present invention provides a ruthenium-based bifunctional fuel cell catalyst and its preparation method and application.
[0004] The technical solution of the present invention is as follows: One of the purposes of the present invention is to provide a method for preparing a ruthenium-based bifunctional fuel cell catalyst, the method comprising: S1: Dissolve glucose hydrate in deionized water, sonicate, add NH4Cl, and continue the reaction to obtain a transparent viscous solution; S2: adding nano-MgO to the transparent viscous solution of S1, drying and calcining after the reaction is completed to obtain porous nitrogen-containing carbon nanospheres wrapped with MgO; S3: grinding the porous nitrogen-containing carbon nanospheres wrapped with MgO in S2, adding H2SO4, acid washing to remove MgO under hydrothermal conditions, washing, filtering, and drying to obtain nitrogen-containing spherical shell-shaped porous nanocarbon materials; S4: dispersing the nitrogen-containing spherical shell porous nanocarbon material described in S3 in deionized water and ethanol, and ultrasonically shaking to obtain a mixed solution; S5: adjusting the pH of the mixed solution of S4 to be alkaline, adding RuCl3 solution, carrying out hydrothermal reaction, washing, filtering, drying, and calcining to obtain a ruthenium-based bifunctional fuel cell catalyst.
[0005] It is further defined that the mass ratio of glucose hydrate to deionized water in S1 is 1:1-1.5, and the mass ratio of glucose hydrate to NH4Cl is 1-2:1.
[0006] It is further defined that the mass ratio of nano-MgO of S2 to glucose hydrate of S1 is 2-3:1.
[0007] Further, the calcination conditions of S2 are as follows: the heating rate is 5 °C min-1 under Ar flow. -1 , heat to 800-900℃, calcination time is 1-2h.
[0008] It is further defined that the H2SO4 concentration of S3 is 1 mol / L.
[0009] It is further defined that the hydrothermal reaction temperature of S3 is 80-85°C and the reaction time is 10-12h.
[0010] It is further defined that the concentration of nitrogen-containing spherical shell porous nanocarbon material in S4 is 0.4-1wt%, and the concentration of ethanol is 15-20wt%.
[0011] Further, the pH value of S5 is 8-9, the concentration of RuCl3 solution is 1wt%, the hydrothermal reaction temperature is 120-130℃, the time is 10-12h, and the calcination condition is a heating rate of 5℃min under H2 flow. -1 , the temperature is raised to 300-500°C, the calcination time is 1-2h, and the Ru loading is 0.4-1wt%.
[0012] A second object of the present invention is to provide a ruthenium-based bifunctional fuel cell catalyst, wherein the ruthenium-based bifunctional fuel cell catalyst is prepared by the above-mentioned preparation method.
[0013] The third object of the present invention is to provide an application of the above-mentioned ruthenium-based bifunctional fuel cell catalyst in a fuel cell.
[0014] Compared with the prior art, the specific advantages of the present invention are as follows: (1) The ruthenium-based bifunctional fuel cell catalyst provided by the present invention has a large specific surface area and rich pore structure, which is beneficial to the actual mass transfer and application of fuel cells. The catalyst exhibits excellent electrocatalytic activity and stability in oxygen reduction reaction and hydrogen oxidation reaction under acidic medium. After being assembled into a hydrogen-oxygen fuel cell, the actual discharge performance of the ruthenium-based bifunctional fuel cell catalyst prepared by the present invention can reach 70% of that of the platinum-based catalyst. Moreover, the price of ruthenium is only about 10% of that of platinum, which can realize the use of ruthenium to replace platinum and reduce the cost of fuel cells; (2) The ruthenium-based bifunctional fuel cell catalyst prepared by the present invention can be used as a catalyst for the cathode and anode of a fuel cell, and has the dual properties of oxygen reduction and hydrogen oxidation. The preparation method of the present invention is simple, easy to operate, and is conducive to industrial production; (3) The present invention uses the method of glucose wrapping hard template nano-MgO to prepare nitrogen-containing spherical shell porous nano-carbon materials for the first time. NH4Cl is used as a nitrogen source and precursor, and its volatility at high temperature is used to generate a large number of pore structures in the carbon material, while also increasing the N content of the material. Ruthenium is attached to the nitrogen-containing spherical shell porous nano-carbon material by hydrothermal and high-temperature reduction reactions, thereby forming a ruthenium-based bifunctional fuel cell catalyst with multiple active sites. The nitrogen-containing spherical shell porous nano-carbon material can be used as a catalyst for the cathode and anode of the fuel cell through the combined action of N, C and loaded ruthenium in the nitrogen-containing spherical shell porous nano-carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 X-ray single crystal diffraction patterns of MgO@p-CNS, @p-CNS / N, @Ru / NC·H2O and Ru / NC in Example 1; Figure 2 (a) is the SEM morphology of MgO@p-CNS in Example 1. Figure 2 (b) is the SEM morphology of @p-CNS / N in Example 1. Figure 2 (c) is the SEM morphology of @Ru / NC·H2O in Example 1. Figure 2 (d) is the SEM morphology of Ru / NC in Example 1; Figure 3 (a) and Figure 3 (b) is a spherical aberration scanning electron microscope morphology of Ru / NC in Example 1. Figure 3 (c) is the Ru element distribution diagram of Example 1Ru / NC, Figure 3 (d) is the C element distribution diagram of Ru / NC in Example 1. Figure 3 (e) is the N element distribution diagram of Ru / NC in Example 1. Figure 3 (f) is the O element distribution diagram of Ru / NC in Example 1; Figure 4(a) is the XPS graph of the entire Ru / NC element in Example 1. Figure 4 (b) is the N element valence distribution diagram of Ru / NC in Example 1, Figure 4 (c) is the Ru element valence distribution diagram of Ru / NC in Example 1; Figure 5 (a) is a BET specific surface area diagram of Ru / NC in Example 1 and Ru / C in Comparative Example 1, Figure 5 (b) is the pore size distribution diagram of Ru / NC in Example 1 and Ru / C in Comparative Example 1; Figure 6 (a) is the ORR voltammogram of Ru / NC in Example 1 and Pt / C in Comparative Example 1 in acidic medium, Figure 6 (b) is a polarization curve diagram of Ru / NC in Example 1 and Pt / C in Comparative Example 1 in an acidic medium; Figure 7 HOR polarization curves of Ru / NC in Example 1 and Pt / C in Comparative Example 1 in acidic medium; Figure 8 This is the steady-state test polarization curve of the hydrogen-oxygen fuel cell prepared in Example 1. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0018] Embodiment 1: Preparation of nitrogen-containing spherical shell porous nanocarbon materials: 1gC6H 12 O6·H2O was dissolved in 1 mL of deionized water and ultrasonically vibrated evenly. 0.5 g of NH4Cl was added and the reaction continued to obtain a transparent viscous solution. 2 g of nano-MgO was added and vibrated for 0.5 h. The solution was then placed in a vacuum drying oven at 90 °C and dried for 10 h. The solution was then placed in a tube furnace and heated at 5 °C min under Ar conditions. -1 The heating rate was raised to 850 °C and kept at this temperature for 1.5 h, and the obtained product was recorded as MgO@p-CNS; 3.5 g of MgO@p-CNS was ground thoroughly with a mortar, and then 100 mL of 1 mol / L H2SO4 solution was added and stirred for 12 h in a water bath at 85 °C to remove nano-MgO. After acid washing, it was rinsed with deionized water 3 times, then rinsed with anhydrous ethanol 2 times, and finally dried in a vacuum oven at 60 °C for 8 h to obtain nitrogen-containing spherical shell porous nanocarbon materials, which were recorded as @p-CNS / N.
[0019] Preparation of ruthenium-based bifunctional fuel cell catalysts: 0.5 g @p-CNS / N was dispersed in 100 mL of deionized water and 20 mL of ethanol, ultrasonically shaken, and the pH was adjusted to 9 with ammonia water. 2.5 mL of 1% RuCl3 solution was added, and the mixture was hydrothermally reacted at 130 °C for 10 h. The mixture was diluted with 100 mL of deionized water and ultrasonically dispersed for 30 min. The mixture was filtered, rinsed with deionized water for 3 times, and then rinsed with anhydrous ethanol for 2 times. Finally, the mixture was dried in a vacuum oven at 60 °C for 8 h. The obtained product was recorded as @Ru / NC·H2O. Weigh 0.2g @Ru / NC·H2O into a porcelain boat, put it into a tube furnace, and heat it at 5℃min under H2. -1 The heating rate was raised to 500°C and kept at this temperature for 1 h to obtain a ruthenium-based bifunctional fuel cell catalyst, which was denoted as Ru / NC.
[0020] Preparation of ruthenium-based bifunctional fuel cells: Take 6 mg of Ru / NC, 50 μL of 5% perfluorosulfonic acid polymer solution (Nafion solution) and 0.95 mL of ethanol solution to prepare the electrochemical test ink solution (ink solution), and ultrasonically disperse it for 2 hours. Select a glassy carbon electrode with a diameter of 5 mm, drop 20 μL of ink solution (ink solution) on the glassy carbon electrode, and dry it naturally to make a test electrode. At this time, the catalyst loading of the electrode head is 0.6 mg cm -2 , for subsequent testing.
[0021] Comparative Example 1: Preparation of Ru / C: The difference between Comparative Example 1 and Example 1 is that NH4Cl is not added in the step of preparing the nitrogen-containing spherical shell-shaped porous nanocarbon material, and the other steps are the same as those in Example 1.
[0022] Comparative Example 2: Preparation of commercial Pt / C electrodes: Weigh 5 mg 20% commercial Pt / C, add 50 μL of 5% perfluorosulfonic acid polymer solution (Nafion solution) and 0.95 mL of isopropanol, and ultrasonically disperse for 1 hour to obtain a mixed solution. Take 4 μL of the mixed solution and drop it on a 5 mm glassy carbon electrode and dry it naturally. At this time, the Pt / C electrode loading is 20 μg (Pt)cm -2 .
[0023] Figure 1 The X-ray single crystal diffraction patterns of MgO@p-CNS, @p-CNS / N, @Ru / NC·H2O and Ru / NC in Example 1 are shown in Table 1. Figure 1 It can be seen that this experiment successfully removed the MgO template and successfully prepared the Ru / NC catalyst.
[0024] Figure 2 (a) is the SEM morphology of MgO@p-CNS in Example 1. Figure 2 (b) is the SEM morphology of @p-CNS / N in Example 1. Figure 2 (c) is the SEM morphology of @Ru / NC·H2O in Example 1. Figure 2 (d) is the SEM morphology of Ru / NC in Example 1. Figure 2 It can be seen that the Ru / NC catalyst prepared in this experiment has a spherical shell structure and has a higher specific surface area, which is beneficial to the actual mass transfer and application of fuel cells.
[0025] Figure 3 (a) and Figure 3 (b) is a spherical aberration scanning electron microscope morphology of Ru / NC in Example 1. Figure 3 (c) is the element distribution diagram of Ru / NC in Example 1. Figure 3 (a) and Figure 3 In (b), we can see that the single-atom ruthenium is evenly distributed on the spherical shell nanocarbon material. Figure 3 Middle (c), Figure 3 Middle (d), Figure 3 Middle (e) and Figure 3 In (f), it can be seen that ruthenium, nitrogen and oxygen elements are evenly distributed on the spherical shell-shaped nanocarbon material.
[0026] Figure 4 (a) is the XPS graph of the entire Ru / NC element in Example 1. Figure 4 (b) is the N element valence distribution diagram of Ru / NC in Example 1, Figure 4 (c) is the Ru element valence distribution diagram of Ru / NC in Example 1. Figure 4 From (b), we can see that the catalyst contains pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen. Figure 4 As shown in (c), the valence states of ruthenium are mainly 0 and +2, which indicates that there are different ruthenium-based active sites in the catalyst.
[0027] Figure 5 (a) is a BET specific surface area diagram of Ru / NC in Example 1 and Ru / C in Comparative Example 1, Figure 5(b) is the pore size distribution diagram of Ru / NC in Example 1 and Ru / C in Comparative Example 1. Figure 5 It can be seen that by adding NH4Cl as a precursor and introducing N into the catalyst, a catalyst with a larger specific surface area and richer pore structure can be obtained.
[0028] Figure 1-5 All physical characterizations prove that the present invention successfully prepares the spherical shell-shaped nano nitrogen-containing catalyst Ru / NC, and Ru / NC has a large specific surface area and rich pore structure, which are beneficial to the actual mass transfer and application of fuel cells.
[0029] Figure 6 (a) is the ORR voltammogram of Ru / NC in Example 1 and Pt / C in Comparative Example 1 in acidic medium, Figure 6 (b) is the polarization curve of Ru / NC in Example 1 and Pt / C in Comparative Example 1 under acidic medium. CV test characterization was performed using Shanghai Chenhua CHI730e electrochemical workstation. Under the test conditions of 0.1 mol / L HClO4 in acidic medium, O2 was continuously introduced for 0.5 h to saturate it. The LSV polarization curve was measured at a speed of 1600 rpm and a scan rate of 10 mVs -1 .Depend on Figure 6 It can be seen that in acidic medium, the half-wave potential of Example 1Ru / NC is only 61 mV less than that of Comparative Example 2Pt / C, showing good electrocatalytic activity.
[0030] Figure 7 The HOR polarization curves of Example 1Ru / NC and Comparative Example 2Pt / C in acidic medium. LSV test characterization was performed using Shanghai Chenhua CHI730e electrochemical workstation. Under the test conditions of 0.1 mol / L HClO4 in acidic medium, H2 was continuously introduced for 0.5h to saturate it. The LSV polarization curve was measured at a speed of 2500rpm and a scan rate of 10mVs -1 .Depend on Figure 7 It can be seen that in acidic medium, the polarization curve of Example 1Ru / NC is similar to the polarization curve of Comparative Example 2Pt / C, and the half-wave potential differs by only 61 mV, which proves that the catalytic performance is similar.
[0031] Figure 8 The steady-state test polarization curve of the hydrogen-oxygen fuel cell prepared in Example 1. The Ru / NC of Example 1 was used as cathode and anode catalysts in a PEMFC system to evaluate its practical application effect. The preparation method of the positive and negative electrodes of the battery is as follows: 30 mg and 3 mg of Ru / NC were weighed, 600 mg of 5 wt% perfluorosulfonic acid polymer solution (Nafion solution) and 600 mg of isopropanol solution were added respectively, ultrasonically dispersed for 2 hours to form a uniform slurry, and the catalyst was coated on the prepared microporous layer with a scraper, and finally 4.0 mg cm was weighed to prepare.-2 The cathode electrode and 0.4mgcm -2 Similarly, a Pt / C anode electrode was prepared, and the Pt loading was controlled at 0.4 mg cm -2 The prepared cathode electrode and anode electrode were hot pressed at 130°C and 30kgf for 120s to form a sandwich structure MEA. The battery performance was tested in a hydrogen-oxygen fuel cell mold. The polarization curve is shown in Figure 8 As shown. Figure 8 It can be seen that the maximum output power of Ru / NC in Example 1 on H2-O2 battery can reach 618mWcm -2 , which is about 71% of Pt / C, showing very good battery performance. Therefore, the Ru / NC prepared in this experiment can replace Pt / C as the anode and cathode catalysts of fuel cells.
[0032] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a ruthenium-based bifunctional fuel cell catalyst, characterized in that: The method: S1: Dissolve glucose hydrate in deionized water, sonicate, add NH4Cl, and continue the reaction to obtain a transparent viscous solution; S2: adding nano-MgO to the transparent viscous solution of S1, drying and calcining after the reaction is completed to obtain porous nitrogen-containing carbon nanospheres wrapped with MgO; S3: grinding the porous nitrogen-containing carbon nanospheres wrapped with MgO in S2, adding H2SO4, acid washing to remove MgO under hydrothermal conditions, washing, filtering, and drying to obtain nitrogen-containing spherical shell-shaped porous nanocarbon materials; S4: dispersing the nitrogen-containing spherical shell porous nanocarbon material described in S3 in deionized water and ethanol, and ultrasonically shaking to obtain a mixed solution; S5: adjusting the pH of the mixed solution of S4 to be alkaline, adding RuCl3 solution, carrying out hydrothermal reaction, washing, filtering, drying, and calcining to obtain a ruthenium-based bifunctional fuel cell catalyst.
2. The method according to claim 1, characterized in that The mass ratio of glucose hydrate to deionized water in S1 is 1:1-1.5, and the mass ratio of glucose hydrate to NH4Cl is 1-2:
1.
3. The method according to claim 1, characterized in that The mass ratio of nano-MgO in S2 to glucose hydrate in S1 is 2-3:
1.
4. The method according to claim 1, characterized in that The calcination conditions of S2 were as follows: the heating rate was 5 °C min-1 under Ar flow. -1 , heat to 800-900℃, calcination time is 1-2h.
5. The method according to claim 1, characterized in that The H2SO4 concentration of S3 is 1 mol / L.
6. The method according to claim 1, characterized in that The hydrothermal reaction temperature of S3 is 80-85°C and the reaction time is 10-12h.
7. The method according to claim 1, characterized in that The concentration of nitrogen-containing spherical shell porous nanocarbon material in S4 is 0.4-1wt%, and the concentration of ethanol is 15-20wt%.
8. The method according to claim 1, characterized in that The pH value of S5 is 8-9, the concentration of RuCl3 solution is 1wt%, the hydrothermal reaction temperature is 120-130℃, the time is 10-12h, and the calcination condition is that the heating rate is 5℃min under H2 flow. -1 , the temperature is raised to 300-500°C, the calcination time is 1-2h, and the Ru loading is 0.4-1wt%.
9. A ruthenium-based bifunctional fuel cell catalyst, characterized in that: The ruthenium-based bifunctional fuel cell catalyst is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the ruthenium-based bifunctional fuel cell catalyst according to claim 9 in a fuel cell.
Citation Information
Patent Citations
Cellular morphology lithium-air battery anode with hierarchical porous structure, and preparation method thereof
CN103219526A
Porous carbon material loaded with ruthenium nanoparticles, and preparation method and application thereof
CN108160073A
Transition metal / nitrogen-doped porous carbon nanosphere electrocatalyst and preparation method thereof
CN110911697A
Carbon-supported platinum-ruthenium catalyst and preparation method thereof
CN115692737A
